Preliminary symptoms assessment of typical faults related to the fans and humidifiers of HVAC systems based on experimental data collected during Italian summer and winter. Issue 1 (November 2021) - Rosato, A; Guarino, F; Youssef, M El; Sibilio, S; Maffei, L
Abstract: The symptoms associated to the occurrence of typical faults in a heating, ventilation and air-conditioning (HVAC) system, including a single duct dual fan constant air volume air-handling unit, have been experimentally characterized. The operation of the HVAC unit with 3 artificially forced faults ((1) reduced velocity of the supply air fan, (2) reduced velocity of the return air fan, (3) the valve supplying the humidifier kept always closed) has been analysed and compared with that of healthy operation of the same plant under very similar boundary conditions (outside air temperature and initial indoor air temperature) during Italian summer and winter in order to preliminarily assess (i) the effects on the main operating parameters, and (ii) generate preliminary operation data to assist further research in fault detection and diagnosis of HVAC systems.